MELESTARIKAN WARISAN LELUHUR: UPAYA MASYARAKAT BADUY LUAR MENJAGA BUDAYA - Hairul Uyun; Sapriya; Encep Supriyatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Baduy Luar community, as one of Indonesia's indigenous groups, is struggling to preserve their cultural identity amidst the rapid pace of modernization. This article delves into how the unique social structure of the Baduy Luar, rooted in traditional values and customary leadership, serves as a bulwark against the erosion of their cultural heritage. This research examines the central role of traditional leaders such as the Puun and Jaro in balancing the demands of modernity with the preservation of ancestral values. Through an in-depth analysis of the community's internal dynamics and interactions with the outside world, this article reveals the adaptive strategies adopted by the Baduy Luar to confront the challenges of globalization. Furthermore, this article discusses the external challenges faced by the Baduy Luar community, including natural resource exploitation, infrastructure development, and the impact of tourism. By understanding the complexities of the issues faced by the Baduy Luar, this article offers policy recommendations that can support efforts to preserve their culture and promote sustainable development in the region.